Implementation of the islamic banking system in Kazakhstan and it’s legal regulation (International relations and international law Journal, 2016)
The article examines the historical aspects of the development of the law on Islamic banking, the design principles of islamic banking products in accordance with the civil legislation of Kazakhstan, defines the basic Islamic banking products, regulation of which is provided by Kazakh legislation reflected typical requirements for implementation within the Islamic banking leasing operations, operations subsoil, contracting operations, etc., and describes the activities of the legal basis of Sharia councils in the implementation of islamic banking under the laws of Kazakhstan. The article provides a detailed and meaningful definition and characteristics of the main products of islamic banking, considers the problems and prospects of development of legal regulation of islamic banks, the creation of a legal framework in Kazakhstan for islamic banks. In addition, the paper investigates further steps to improve the Institute of Islamic banking in Kazakhstan.
Keywords: islamic banking system; islamic financial institutions; the rules and principles of islamic law; islamic financing; islamic financial instruments